Impact of Behavior Change Communications and Market-based Approach to Delivering Micronutrient Powders on Stunting, Infant Feeding Practices and Anemia in Bangladesh - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
This study seeks to assess the acceptability, compliance, and preference for iron supplementation; micronutrient powders (MNP) versus iron syrup. Additionally, this study seeks to assess front line health worker perceptions and experiences regarding ease of implementation of each strategy and delivery strategy preference.